Toward the Development of a Universal Outcome Instrument for Spine Trauma: A Systematic Review and Content Comparison of Outcome Measures Used in Spine Trauma Research Using the ICF as Reference. Issue 4 (February 2016) - Oner, F. Cumhur; Jacobs, Wilco C.H.; Lehr, A. Mechteld; Sadiqi, Said; Post, Marcel W.; Aarabi, Bizhan; Chapman, Jens R.; Dvorak, Marcel F.; Fehlings, Michael G.; Kandziora, Frank; Rajasekaran, S.; Vaccaro, Alexander R.
Abstract : Study Design: A systematic literature review. Objective: The aim of this study was (1) to identify patient-reported and clinician-based outcome measures most frequently used to evaluate the function and health of spine trauma patients, (2) to identify and quantify the concepts of these measures using the International Classification of Functioning, Disability, and Health (ICF) as reference, and (3) to describe their clinimetric properties. Summary of Background Data: There is a real need for a disease-specific outcome instrument to measure the effect size of various treatment options in a variety of traumatic spinal column injuries. Methods: A systematic literature search was conducted in several databases. From the included studies, outcome measures were extracted. The items and underlying concepts of the identified outcome measures were specified and linked to the ICF categories. Finally, as far as available in literature, the clinimetric properties of the obtained measures were analyzed. Results: Out of 5117 screened references, 245 were included, and 17 different frequently used outcome measures were identified. Meaningful concepts of the items and response options of the retrieved outcome measures were linked to a total of 105 different ICF categories, aggregated to 57 first- or second-level categories. The categories were linked to the components activities and participation (n = 31), body functions (n = 17), environmental factors (n = 8), and body structures (n = 1). Overall, there is only limited evidence on the measurement properties, except for some disease-specific questionnaires, such as Oswestry Disability Index, Roland–Morris Disability Questionnaire, Neck Disability Index, and Cervical Spine Outcome Questionnaire. Conclusion: The current systematic literature review revealed great diversity in the use and content of outcome measures to evaluate the functioning and health of spine trauma patients, with 17 different outcome measures linked to 57 unique ICF categories. This study creates an evidence base for a consensus meeting during which a core set of ICF categories for outcome measurement in spine trauma will be decided. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the text